Edukacja przedszkolna. Pomiędzy paradygmatem technologicznym a humanistycznym - Paprotna, Gabriela (Chowanna, 2019)
Pre-school education, as the first level of general human education, has been an important area in the 40-year work of the Department of Early Childhood Education and Media Pedagogy. During these years, the reality of pre-school education has undergone (and is still undergoing) a peculiar transition from the technological paradigm to the humanistic paradigm. In the technological approach, based on positive philosophy and behaviorism, the axis of education was the curriculum, and its central figure was the teacher. The role of the child consisted in adapting to the curriculum and the requirements of the kindergarten. Children’s needs and their capabilities were not exhibited in the process of education. In the education based on a humanistic approach, derived from anti-intellectual naturalism, pedagogical progressivism and humanistic psychology, the central figure is the child, and the main purpose of education is to support his/her development. The teacher is to be a helper, a guide and is to allow the child to grow according to his/her own developmental potential. Thus, the curriculum no longer plays the most important role, but the child does – the entity. Parents have also been involved in the process of pre-school education, and they have also gained a sense of subjectivity. Due to the fact that changes in education do not take place quickly, and the pre-school education system has been firmly fixed for several decades, it can be said that currently pre-school education is in the stage of searching for its (new) path. Some elements of the technological system are still present, but we also observe many changes towards humanistic, subjective education.